2011
DOI: 10.1007/s10591-011-9148-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Contexts in Adolescent Pregnancy: The Role of Individual, Sociodemographic, Familial and Relational Variables in Understanding Risk of Occurrence and Adjustment Patterns

Abstract: Adolescent pregnancy appears today as an intricate tapestry where different dimensions interact. In our study we examined the associations between individual, sociodemographic, familial, and relational variables and their impact on the occurrence of pregnancy and adolescents' adjustment to it. Participants were Portuguese pregnant and non-pregnant adolescents (N = 833). Ecological contexts were characterized, and individual and relational adjustment (depressive symptoms and quality of life; perceived quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 61 publications
7
22
0
5
Order By: Relevance
“…After the initial response, however, Mary felt supported. Our participants more often cited their mothers and partners as sources of support, reinforcing previous findings about adolescent pregnancy (Araújo-Pedrosa, Pires, Carvalho, Canavarro, & Dattilio, 2011), and HIV (Pereira & Canavarro, 2009). Fathers and friends, on the other hand, were not mentioned.…”
Section: Hiv Diagnosissupporting
confidence: 88%
“…After the initial response, however, Mary felt supported. Our participants more often cited their mothers and partners as sources of support, reinforcing previous findings about adolescent pregnancy (Araújo-Pedrosa, Pires, Carvalho, Canavarro, & Dattilio, 2011), and HIV (Pereira & Canavarro, 2009). Fathers and friends, on the other hand, were not mentioned.…”
Section: Hiv Diagnosissupporting
confidence: 88%
“…However, studies about QoL among pregnant adolescents are scarce and contradictory. While some authors found a negative influence of pregnancy on adolescents' QoL (2), other recent findings have shown no significant effects (25,26) or have shown positive effects, with pregnant adolescents showing higher QoL compared to peers with no pregnancy history (27).…”
Section: Adolescents' Qol During Pregnancymentioning
confidence: 93%
“…Associados ao abandono escolar precoce (Adamczyk, 2008;Evans, 2001;Ourô & Leal, 1998) e à ausência de ponderação das alternativas possíveis face à ocorrência da gravidez (Murry, 1995;Pires, Pereira et al, 2013), estes contextos sociais e ambientais parecem contribuir para que a maternidade adolescente se configure como um projeto de vida válido para a jovem de engravida. Segundo diversos autores, sob estas condições, a maternidade adolescente pode mesmo ser perspetivada como uma via de autonomização e de realização pessoal (Araújo Pedrosa, Pires, Carvalho, Canavarro, & Dattilio, 2011;Murry, 1995). Acresce que, quando a jovem possui afiliação religiosa (Adamczyk, 2008;Evans, 2001) e o seu meio envolvente apresenta um maior grau de religiosidade, parecem estar reunidas condições desfavoráveis à realização de uma IVG.…”
Section: Discussionunclassified
“…Tal facto recomenda alguma prudência na generalização dos resultados da investigação internacional para a realidade sociocultural portuguesa, fornecendo importantes pistas para a investigação futura. A ruralidade é habitualmente sugerida como potenciadora de projetos de vida voltados para a família e para a maternidade na adolescência (Bradshaw et al, 2005;Araújo Pedrosa et al, 2011). De forma congruente com esta perspetiva, alguns estudos nacionais concluem que o planeamento da gravidez adolescente é mais frequente no Alentejo e na Região Autónoma dos Açores , áreas cujos municípios são maioritariamente rurais (INE, 2012).…”
Section: Discussionunclassified